Carbon nanotube dispersion liquid, composite material slurry for electrode, electrode film, and secondary battery

By preparing carbon nanotube dispersion with specific particle size distribution, the problems of short length and poor dispersion of carbon nanotube fibers are solved, high conductivity and time stability are achieved, and the performance of secondary batteries is improved.

CN119325452APending Publication Date: 2025-01-17아티엔스가부시키가이샤 +1

Patent Information

Application Number
CN202380043323.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-21
Filing Date
2023-06-19
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In the prior art, the fiber length of the carbon nanotubes is short and cannot be dispersed stably, resulting in insufficient conductivity and stability over time, and it is difficult for carbon nanotubes with small outer diameter to form high-concentration and good dispersion liquid.

Method used

By preparing a carbon nanotube dispersion with a specific particle size distribution, including multiple carbon nanotubes, the particle size and fiber diameter distribution are measured using laser diffraction/scattering particle size distribution determination method and penetrating electron microscopy, and the fluorine-based resin is added as a dispersant The control particle size distribution is in the range of 0.1 μm to 3 μm and 10 μm to 100 μm, the accumulated particle size D50 is 4 μm or more, and it is stable dispersed in a solvent above pH 8.

Benefits of technology

The carbon nanotube dispersion liquid with high conductivity and time stability is achieved, and is used in the composite material slurry for electrodes and the electrode film, which improves the rate and cycle characteristics of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325452A_ABST
    Figure CN119325452A_ABST
Patent Text Reader

Abstract

Provided is a carbon nanotube dispersion liquid containing carbon nanotubes, a dispersant, and a solvent, the carbon nanotube dispersion liquid having particle size distribution peaks in the particle size range of 0.1 [mu] m to 3 [mu] m and in the particle size range of 10 [mu] m to 100 [mu] m in a volume-based particle size distribution curve measured by a laser diffraction / scattering particle size distribution measurement method, and having particle size distribution peaks in the particle size range of 0.1 [mu] m to 3 [mu] m, and having particle size distribution peaks in the particle size range of 10 [mu] m to 100 [mu] m. And the cumulative particle diameter D50 is 4 [mu] m or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to a carbon nanotube dispersion, an electrode composite material slurry, an electrode film, and a secondary battery. Background Art

[0002] Lithium ion secondary batteries are widely used as batteries for electric vehicles, portable devices, etc. As electric vehicles and portable devices become more advanced in performance, demands for lithium ion secondary batteries to have higher capacity, higher output, and be smaller and lighter are increasing year by year.

[0003] The capacity of lithium-ion secondary batteries depends largely on the positive electrode active material and the negative electrode active material as the main materials, so various materials used for these electrode active materials are being actively studied. However, the charge capacity when using the electrode active materials that have been put into practical use has reached a level close to the theoretical value, and the improvement is close to the limit. Therefore, if the filling amount of the electrode active material in the electrode film is increased, the charge capacity can be simply increased. Therefore, attempts are being made to reduce the amount of conductive materials and binder resins that do not directly contribute to the charge capacity.

[0004] Conductive material is responsible for forming a conductive path inside the electrode film or connecting the particles of the electrode active material, requiring that the connection between the conductive path and the particles is not easy to be cut off due to the expansion and contraction of the electrode film. In order to maintain the connection between the conductive path and the particles with a small addition, by using nano-carbon with a large specific surface area, particularly carbon nanotubes (carbon nanotube, CNT) as a conductive material, an efficient conductive network is efficiently formed. However, the cohesive force of nano-carbon with a large specific surface area is strong, so there is a problem that it is not easy to make nano-carbon well dispersed in the electrode composite slurry and / or the electrode film.

[0005] Under such circumstances, methods of preparing a conductive material dispersion using various dispersants and producing a composite material slurry for an electrode from the conductive material dispersion or methods of studying the physical properties of carbon nanotubes themselves have been proposed (see Patent Documents 1 to 3).

[0006] Patent documents 1 to 3 propose a method for preparing an electrode for a lithium ion battery by using a plurality of conductive materials in combination to suppress the aggregation of conductive materials during dispersion and drying, or to reduce the amount of conductive materials and binder resin added. In addition, generally, the smaller the outer diameter of the carbon nanotube, the larger the specific surface area, so the wettability in the solvent deteriorates, and it is difficult to obtain a high-concentration and good dispersion. However, since the smaller the outer diameter and the higher the specific surface area of ​​the carbon nanotube, the more ideally an efficient conductive network can be formed, it is imperative to obtain a dispersion that, while carrying the conductivity unique to the carbon nanotube and more specifically without breaking its fiber length, effectively utilizes it and disperses it well.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-044820

[0010] Patent Document 2: Japanese Patent Publication No. 2010-238575

[0011] Patent Document 3: Japanese Patent Application Publication No. 2016-025077 Summary of the invention

[0012] Problems to be solved by the invention

[0013] However, the carbon nanotubes in the dispersions obtained in Patent Documents 1 to 3 have short fiber lengths and cannot be dispersed stably while maintaining conductivity. Furthermore, the use of a plurality of carbon nanotubes increases the structural viscosity between the carbon nanotubes, which may increase viscosity or gel over time.

[0014] Therefore, an object of the present invention is to provide a carbon nanotube dispersion having high conductivity and good temporal stability, and to provide a secondary battery having excellent rate characteristics and cycle characteristics by using an electrode composite material slurry and an electrode film using the carbon nanotube dispersion.

[0015] Technical means of solving problems

[0016] The inventors of the present invention have conducted diligent research and have discovered that by preparing a carbon nanotube dispersion liquid comprising a solvent, a dispersant and carbon nanotubes and having a specific particle size distribution characteristic, the conductivity is not impaired even when a plurality of carbon nanotubes are contained, and the stability over time is excellent. When preparing composite material slurry for electrodes and when manufacturing electrode films, the dispersion liquid can be maintained in a good dispersion state and a good conductive network can be formed in the electrode.

[0017] That is, the present invention includes the following embodiments.

[0018] [1] A carbon nanotube dispersion comprising carbon nanotubes, a dispersant, and a solvent, wherein in a volume-based particle size distribution curve measured by a laser diffraction / scattering particle size distribution measurement method, the dispersion has a particle size distribution peak in a range of a particle size of 0.1 μm or more and 3 μm or less, and in a range of a particle size of 10 μm or more and 100 μm or less,

[0019] Cumulative particle size D 50 4μm or more.

[0020] [2] The carbon nanotube dispersion according to [1], wherein in the fiber diameter distribution of the carbon nanotubes measured by a transmission electron microscope, there are at least two fiber diameter distributions in the range of fiber diameter of 0.1 nm to 20 nm.

[0021] [3] The carbon nanotube dispersion according to [2], which has a first fiber diameter distribution in the range of 0.5 nm to less than 3 nm and a second fiber diameter distribution in the range of 3 nm to 10 nm.

[0022] [4] The carbon nanotube dispersion according to any one of [1] to [3], wherein the dispersant contains a fluorine-based resin.

[0023] [5] The carbon nanotube dispersion according to any one of [1] to [4], wherein the mass ratio of the fluorine-based resin to the carbon nanotubes is 0.1 to 10.

[0024] [6] The carbon nanotube dispersion according to any one of [1] to [5], wherein the solvent contains substantially no water and has a pH of 8 to 12.

[0025] [7] A composite material slurry for an electrode, comprising the carbon nanotube dispersion according to any one of [1] to [6], and an electrode active material.

[0026] [8] An electrode film comprising a coating film of the carbon nanotube dispersion according to any one of [1] to [6] or the electrode composite material slurry according to [7].

[0027] [9] A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the electrode film according to [8] is used for at least one of the positive electrode and the negative electrode.

[0028] Effects of the Invention

[0029] According to the embodiment of the present invention, a carbon nanotube dispersion having high conductivity and good temporal stability can be provided, and a secondary battery having excellent rate characteristics and cycle characteristics can be provided by using an electrode composite material slurry and an electrode film using the carbon nanotube dispersion. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a graph showing the particle size distribution of the carbon nanotube dispersion in Example 1 at a laser light transmittance of 60% in the laser diffraction / scattering particle size distribution measurement method.

[0031] Figure 2 This is a graph showing the distribution of fiber diameters of the carbon nanotube dispersion in Example 1 measured by a transmission electron microscope. DETAILED DESCRIPTION

[0032] Hereinafter, carbon nanotubes, carbon nanotube dispersions, composite material slurries for electrodes, electrode films, and secondary batteries, etc., which are embodiments of the present invention, are described in detail. The present invention is not limited to the following embodiments, and the present invention also includes embodiments implemented within the scope of the present invention. In addition, the numerical values ​​determined in this specification are values ​​obtained by the methods disclosed in the embodiments or examples.

[0033] In this specification, conductive materials such as carbon nanotubes and carbon black are sometimes referred to as "conductive materials". In this specification, the fiber diameter of carbon nanotubes is sometimes referred to as "outer diameter". In addition, in this specification, coating films and coating films are sometimes referred to as "electrode films".

[0034] In this specification, the numerical range expressed by "to" indicates a range including the numerical values ​​recorded before and after "to" as the minimum and maximum values, respectively. In the numerical ranges recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of other stages.

[0035] Unless otherwise specified, various components mentioned in the present specification may be used alone or in combination of two or more.

[0036] Carbon Nanotube Dispersion

[0037] The carbon nanotube dispersion of some embodiments comprises carbon nanotubes, a dispersant, and a solvent. In addition, in a volume-based particle size distribution curve measured by a laser diffraction / scattering particle size distribution measurement method, there are particle size distribution peaks in the range of particle diameters of 0.1 μm or more and 3 μm or less, and in the range of particle diameters of 10 μm or more and 100 μm or less, and the cumulative particle size D 50 4μm or more.

[0038] <Carbon Nanotube>

[0039] The carbon nanotube is a shape in which a flat graphite is wound into a cylindrical shape, and includes a single-layer carbon nanotube or a multi-layer carbon nanotube, which can be mixed together. The single-layer carbon nanotube has a structure in which a layer of graphite is wound. The multi-layer carbon nanotube has a structure in which two or more layers of graphite are wound. In addition, the side wall of the carbon nanotube may not be a graphite structure. In addition, for example, in this specification, a carbon nanotube including a side wall having an amorphous structure is also set as a carbon nanotube.

[0040] The shape of the carbon nanotube is not limited. Regarding the shape, various shapes including needle-shaped, cylindrical tube-shaped, fishbone-shaped (fishbone or cup stacking type), card-shaped (platelet) and coil-shaped can be listed. In this embodiment, the shape of the carbon nanotube is preferably needle-shaped or cylindrical tube-shaped. The carbon nanotube can be a single shape or a combination of two or more shapes.

[0041] Examples of the form of carbon nanotubes include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. Carbon nanotubes may have these forms alone or in combination of two or more forms.

[0042] The carbon nanotube dispersion according to some embodiments preferably uses at least two types of carbon nanotubes having different average fiber diameters, and specifically, may include at least a first carbon nanotube and a second carbon nanotube.

[0043] The average fiber diameter of the first carbon nanotube is preferably greater than 0.1 nm, more preferably greater than 0.5 nm, and more preferably greater than 1 nm. In addition, it is preferably less than 5 nm, and more preferably less than 3 nm. For example, the average fiber diameter of the first carbon nanotube may be greater than 0.1 nm and less than 5 nm, greater than 0.5 nm and less than 3 nm, or greater than 1 nm and less than 3 nm. The average fiber diameter of the second carbon nanotube is preferably greater than 3 nm, and more preferably greater than 5 nm. In addition, it is preferably less than 20 nm, and more preferably less than 10 nm. For example, the average fiber diameter of the second carbon nanotube may be greater than 3 nm and less than 20 nm, or greater than 5 nm and less than 10 nm. Regarding the average fiber diameter of the carbon nanotube, the morphology of the carbon nanotube can be observed by a transmission electron microscope, the length of the minor axis can be measured, and it can be calculated based on the average value of 300 carbon nanotubes.

[0044] Specifically, regarding the average fiber diameter of carbon nanotubes, for example, a film can be formed using a diluted solution of carbon nanotubes, and the fiber diameters of 300 randomly extracted carbon nanotubes can be measured using a direct transmission electron microscope (H-7650, manufactured by Hitachi, Ltd.) at a magnification of 50,000 times, and the fiber diameters can be calculated based on the average value.

[0045] The first carbon nanotube is preferably a single-layer carbon nanotube, and the second carbon nanotube is preferably a multi-layer carbon nanotube. The single-layer carbon nanotube has a structure in which one layer of graphite is wound, and the multi-layer carbon nanotube has a structure in which two or more layers of graphite are wound.

[0046] The first carbon nanotube is a carbon material with strong cohesion and poor dispersibility, and because of its high linearity, it is believed that it helps conduction between active materials that are relatively far apart in the electrode layer, but the probability of contact with the active material is relatively low. On the other hand, the second carbon nanotube is a carbon material with weak cohesion and good dispersibility, and because of its low linearity, it is believed that it helps conduction between active materials that are relatively close, and the probability of contact with the active material is relatively high.

[0047] The mass ratio of the first carbon nanotube to the second carbon nanotube is 1:10 to 20:1, preferably 1:9 to 10:1, and more preferably 1:5 to 5:1. Within the above range, a carbon nanotube dispersion having good dispersibility, excellent conduction between active materials, high contact probability with active materials, and excellent peel strength (adhesion) can be obtained to form an electrode layer.

[0048] The carbon purity of the carbon nanotubes is represented by the content (mass %) of carbon atoms in the carbon nanotubes. The carbon purity is preferably 80 mass %, more preferably 90 mass %, more preferably 95 mass %, and particularly preferably 98 mass % or more relative to 100 mass % of the carbon nanotubes. By making the carbon purity within the above range, it is possible to prevent the formation of dendrites due to impurities and causing short circuits and other undesirable conditions.

[0049] The carbon purity of carbon nanotubes can be adjusted by purification treatment. As the purification treatment method of carbon nanotubes, various conventionally known methods can be used. For example, acid treatment, graphitization treatment, and chlorination treatment can be mentioned.

[0050] The acid used when the carbon nanotubes are subjected to the acid treatment may be any acid that can dissolve the metal and metal oxide contained in the carbon nanotubes, and is preferably an inorganic acid and a carboxylic acid, and among the inorganic acids, hydrochloric acid, sulfuric acid, and nitric acid are particularly preferred. The acid treatment of the carbon nanotubes is preferably carried out in a liquid phase, and more preferably, the carbon nanotubes are dispersed and / or mixed in a liquid phase. The carbon nanotubes after the acid treatment are preferably washed with water and dried.

[0051] The graphitization treatment of the carbon nanotubes is not particularly limited, and can be performed by heating the carbon nanotubes at 1500° C. to 3500° C. in an inert atmosphere having an oxygen concentration of 0.1% or less.

[0052] The chlorination treatment of the carbon nanotubes is not particularly limited, and can be performed, for example, by introducing chlorine gas in an inert atmosphere having an oxygen concentration of 0.1% or less and heating the carbon nanotubes at 800° C. to 2000° C.

[0053] The surface or end of the carbon nanotube can be modified with a functional group or an alkyl group, and can also be doped with an alkali metal or a halogen. For example, by heating in an acid, the carbon nanotube can be functionalized with a carboxyl group, a sulfonic group, or a hydroxyl group.

[0054] As the conductive material, one or more carbon materials such as carbon black and graphite may also be used in combination. Among these conductive materials, carbon black is preferably used from the viewpoint of the adsorption performance of the dispersant. Examples of carbon black include acetylene black, furnace black, hollow carbon black, channel black, thermal black, Ketjen black, etc. In addition, carbon black may be any one of neutral, acidic, and alkaline, and oxidized carbon black and graphitized carbon black may also be used.

[0055] <Dispersant>

[0056] The dispersant of the present embodiment is not particularly limited within the range that can stabilize the dispersion of carbon nanotubes, and surfactants and resin-type dispersants can be used. Surfactants are mainly classified into anionic, cationic, nonionic and amphoteric. A preferred type of dispersant can be used appropriately in a preferred amount according to the characteristics required for the dispersion of carbon nanotubes.

[0057] When anionic surfactants are selected, their types are not particularly limited. Specifically, fatty acid salts, polysulfonates, polycarboxylates, alkyl sulfate ester salts, alkyl aryl sulfonates, alkyl naphthalene sulfonates, dialkyl sulfonates, dialkyl sulfosuccinates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkyl aryl ether sulfates, naphthalenesulfonic acid formalin condensates, polyoxyethylene alkyl phosphoric acid sulfonates, glycerol borate fatty acid esters and polyoxyethylene glycerol fatty acid esters can be listed, but they are not limited to these. Furthermore, specifically, sodium dodecylbenzene sulfonate, sodium laurate sulfate, sodium polyoxyethylene lauryl ether sulfate, polyoxyethylene nonylphenyl ether sulfate salts and sodium salts of β-naphthalenesulfonic acid formalin condensates can be listed, but they are not limited to these.

[0058] In addition, as cationic surfactants, there are alkylamine salts and quaternary ammonium salts. Specifically, stearylamine acetate, trimethyl coconut oil ammonium chloride, trimethyl tallow ammonium chloride, dimethyl dioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly (vinyl pyridine) - dodecyl bromide and dodecyl benzyl triethyl ammonium chloride can be listed, but it is not limited to these. In addition, as amphoteric surfactants, aminocarboxylates can be listed, but it is not limited to these.

[0059] In addition, as nonionic surfactants, polyoxyethylene alkyl ethers, polyoxyalkylene derivatives, polyoxyethylene phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters and alkyl allyl ethers can be listed, but they are not limited to these. Specifically, polyoxyethylene lauryl ether, sorbitan fatty acid esters and polyoxyethylene octyl phenyl ether can be listed, but they are not limited to these.

[0060] The selected surfactant is not limited to a single surfactant. Therefore, two or more surfactants can be used in combination. For example, a combination of anionic surfactant and nonionic surfactant, or a combination of cationic surfactant and nonionic surfactant can be used. The blending amount at this time is preferably set to a preferred blending amount relative to each surfactant component. As a combination, a combination of anionic surfactant and nonionic surfactant is preferred. The anionic surfactant is preferably a polycarboxylate. The nonionic surfactant is preferably polyoxyethylene phenyl ether.

[0061] In addition, as the resin type dispersant, specifically, fluorine resin, cellulose derivatives (cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, etc.), polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, hydrogenated nitrile rubber, polyacrylonitrile polymer, etc. are listed. Fluorine resin, methyl cellulose, ethyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, hydrogenated nitrile rubber, polyacrylonitrile polymer are particularly preferred. The molecular weight of the resin type dispersant is preferably 10,000 to 3,000,000.

[0062] Fluorine resins may include structures in which hydrogen of polyethylene is replaced by fluorine or trifluoromethyl. Examples of fluorine resins include homopolymers such as polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVdF), and polychlorotrifluoroethylene (PCTFE); copolymers such as perfluoroalkoxyalkane (PFA), perfluoroethylene propene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), and tetrafluoroethylene-perfluorodioxysoap copolymer (tetrafluoroethylene / perfluoro(2,2-dimethyl-1,3-dioxole) copolymer (TPE / PDD)). They can be used alone or in combination of two or more. In fluorine-based resins, in terms of resistance, preferably polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVdF), resins with their structural units, their modified substances or combinations thereof. Among them, preferably polyvinylidene fluoride resins, for example, homopolymers of polyvinylidene fluoride can be listed; copolymers of vinylidene fluoride and hexafluoropropylene, tetrafluoroethylene, etc. Polyvinylidene fluoride resins can be modified, for example, acidic groups such as carboxyl groups can be introduced. Fluorine-based resins can be used alone or in combination of two or more.

[0063] In order to maintain resistance and adhesion with resin viscosity in a good balance, the weight average molecular weight (Mw) of the fluororesin is preferably 100,0000 to 5,000,000, more preferably 200,000 to 3,000,000, and even more preferably 500,000 to 1,500,000. From the viewpoint of film forming properties of the electrode film, the glass transition point of the fluororesin is preferably 20°C or less, more preferably 10°C or less, and even more preferably 0°C or less.

[0064] Examples of commercially available products of polyvinylidene fluoride and modified products thereof include KF polymer series "W#7300, W#7200, W#1700, W#1300, W#1100, W#9700, W#9300, W#9100, L#7305, L#7208, L#1710, L#1320, L#1120" manufactured by Kureha Co., Ltd. and Solef series "6008, 6010, 6012, 1015, 6020, 5130, 9007, 460, 41308, 11010, 21510, 31508, 60512" manufactured by Solvay (all trade names).

[0065] From the viewpoint of the oxidation resistance of the dispersant, hydrogenated nitrile rubber, polyacrylonitrile polymer, and fluorine-based resin are preferred.

[0066] Among these, the dispersant is particularly preferably a fluorine resin. From the viewpoint of making a plurality of carbon nanotubes with different particle size distributions uniformly dispersed and stably present, and from the viewpoint of balancing the adsorption capacity of carbon nanotubes with the affinity of the solvent, a fluorine resin is preferably used. In addition, the fluorine resin functions not only as a dispersant for carbon nanotubes, but also as a binder resin. By using a fluorine resin as a dispersant, even in the process of preparing a composite slurry by mixing other binder components or active substances, and then applying and drying to form a film, the carbon nanotubes in the dispersion can be kept in a uniformly dispersed state, and a long conductive path can be formed. In addition, for carbon nanotubes 1, the mass ratio of the fluorine resin to the carbon nanotubes is preferably 0.1 to 10, more preferably 0.5 to 8, and further preferably 1 to 5. By being within the range, a uniform dispersion with excellent conductivity can be obtained.

[0067] In addition, in addition to the dispersant, it is preferred to add an amine compound or an inorganic base. As the amine compound, a first amine (primary amine), a second amine (secondary amine), and a third amine (tertiary amine) are used, and ammonia or quaternary ammonium compounds are not included. In addition to monoamines, amine compounds such as diamines, triamines, and tetramines having multiple amino groups in the molecule can also be used. Specifically, for example, aliphatic primary amines such as methylamine, ethylamine, butylamine, and octylamine, aliphatic secondary amines such as dimethylamine, diethylamine, and dibutylamine, aliphatic tertiary amines such as trimethylamine, triethylamine, and dimethyloctylamine, alanine, methionine, proline, serine, asparagine, glutamine, lysine, arginine, histidine, aspartic acid, glutamic acid, cysteine, dimethylaminoethanol, monoethanolamine, diethanolamine, methylethanolamine, triethanolamine, alkanolamines such as triethanolamine, hexamethylenetetramine, morpholine, piperidine, etc. can be listed, but it is not limited to these. Examples of the inorganic base include alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkaline earth metal carbonates, alkali metal phosphates, and alkaline earth metal phosphates.

[0068] From the viewpoint of dispersion stability of carbon nanotubes, the content of the dispersant is preferably 10 to 1000 parts by mass, more preferably 20 to 500 parts by mass, relative to 100 parts by mass of carbon nanotubes. By setting the content within the above range, the carbon nanotubes having different dispersibilities can be kept in a good dispersion state.

[0069] <Solvent>

[0070] The solvent of the present embodiment is not limited as long as it is a solvent capable of dispersing carbon nanotubes, and organic solvents such as water or amide-based organic solvents can be used. From the perspective of the wettability of carbon nanotubes, it is preferred to use an amide-based organic solvent. As amide-based organic solvents, there are: N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc. In particular, it is more preferred to include at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone.

[0071] When an organic solvent is used as a solvent, it is preferably substantially free of water from the viewpoint of suppressing the thickening of carbon nanotubes. Specifically, based on the carbon nanotube dispersion, the water content is preferably 100ppm to 3000ppm, more preferably 200ppm to 1500ppm, and preferably less than 1000ppm. If a large amount of water is contained, it may sometimes have an adverse effect on the thickening or gelation of the carbon nanotube dispersion or the composite material slurry for electrodes using the carbon nanotube dispersion or the composite material slurry, but by being within the range, the carbon nanotubes with different dispersivities can be kept in a good dispersed state, reducing the problem of thickening of the carbon nanotube dispersion during storage.

[0072] <Other optional ingredients>

[0073] The carbon nanotube dispersion of some embodiments may be appropriately formulated with other additives such as wetting agents, surfactants, pH adjusters, wetting and penetrating agents, leveling agents, and other conductive materials as needed within the scope that does not hinder the purpose of the present invention. The additives may be added at any time, such as before preparing the dispersion, during dispersion, after dispersion, or during preparation of the electrode forming composition.

[0074] <Method for producing carbon nanotube dispersion>

[0075] The method for producing the carbon nanotube dispersion is not particularly limited. For example, it is preferably produced by finely dispersing a mixture using a dispersing device, wherein the mixture includes carbon nanotubes, a dispersant, a solvent, and any components as required. The carbon nanotube dispersion of some embodiments preferably includes at least two carbon nanotubes, each of which can be dispersed at the same time, or a pre-dispersion liquid dispersed separately can be produced, and these pre-dispersion liquids can be mixed to produce the carbon nanotube dispersion. In addition, the dispersion treatment can arbitrarily adjust the timing of adding the materials used, and set it as a multi-stage treatment of more than two times.

[0076] As the dispersing device, a dispersing machine commonly used in pigment dispersion, etc. can be used. For example, dispersing machines, homomixers, planetary mixers and other mixers, homogenizers (Advanced Digital Sonifer (registered trademark), Model (MODEL) 450DA manufactured by BRANSON, "Clearmix" manufactured by M-technique, "Filmix" manufactured by PRIMIX, "Abramix" manufactured by Silverson, etc.), paint conditioners (manufactured by Red Devil), colloid mills ("PUC colloid mill" manufactured by PUC, "Colloid mill MK" manufactured by IKA), cone mills ("Cone mill MKO" manufactured by IKA, etc.), ball mills, sand mills (SHINMARU Media type dispersers such as "Dyno-mill" manufactured by ENTERPRISES, etc.), attritor, pearl mill ("DCPmill" manufactured by Eirich, etc.), co-ball mill, high pressure homogenizer ("Jenius PY" manufactured by Jenius, "Star burst" manufactured by SUGINO Machine, "nanomizer" manufactured by Nanomizer, etc.), media-free dispersers such as "Clear SS-5" manufactured by M-technique, "MICROS" manufactured by Nara Machinery, and other roll mills, etc. In particular, from the perspective of promoting wetting of carbon nanotubes and untangling rough particles, it is more preferable to use a high shear mixer or a bead mill in the initial step of dispersion, and further from the perspective of subsequently dispersing the conductive material while maintaining its aspect ratio, to use a high-pressure homogenizer.

[0077] There are batch dispersion, through dispersion, circulation dispersion, etc. in the dispersion method using a dispersion device, but any method can be used, and two or more methods can be combined. The so-called batch dispersion is a method of dispersing using only the dispersion device body without using piping, etc. Because of its simple operation, it is preferred in the case of small-scale production. The so-called through dispersion is a dispersion method in which the dispersion device body includes a tank for supplying the dispersed liquid via piping and a tank for receiving the dispersed liquid, and the dispersed liquid passes through the dispersion device body. In addition, the so-called circulation dispersion is a method of returning the dispersed liquid that has passed through the dispersion device body to the tank for supplying the dispersed liquid, and dispersing while circulating. In any method, the longer the processing time is extended, the more dispersion is performed. Therefore, as long as the passing or circulation is repeated until the target dispersion state is reached, the processing volume can be increased by changing the size of the tank or the processing time. Compared with the circulation dispersion, through dispersion is preferred in terms of the ease of making the dispersion state uniform. Compared with the through dispersion, the circulation dispersion is preferred in terms of the simplicity of operation or manufacturing equipment. The dispersion process sequentially or simultaneously performs the crushing of aggregated particles, the disentanglement, wetting, stabilization, etc. of the conductive material. Depending on the method of performing the process, the dispersion state of the finished product is different, so it is preferred to manage the dispersion state in each dispersion process by using various evaluation methods. For example, the method described in the embodiment can be used for management.

[0078] CNTs with large fiber lengths are uniformly and well dispersed while maintaining the length above a certain level, thereby forming a developed conductive network. In particular, the carbon nanotube dispersions of some embodiments can form an efficient conductive network by becoming the following state, namely: two types of carbon nanotubes with different outer diameters (fiber diameters) and fiber lengths, i.e., different dispersities, are dispersed and stably untied in a state of being appropriately maintained without breaking each fiber with a particularly appropriate dispersion. Therefore, it is not simply necessary that the viscosity of the carbon nanotube dispersion is low and the (apparent) dispersibility is good. It is particularly effective to combine the complex elastic modulus and phase angle with previous indicators such as viscosity to judge the dispersion state. By setting the complex elastic modulus and phase angle to the range described later, a carbon nanotube dispersion with good conductivity and electrode strength can be obtained.

[0079] [Particle size distribution characteristics]

[0080] The carbon nanotube dispersion of some embodiments has a particle size distribution peak in the range of 0.1 μm to 3 μm and in the range of 10 μm to 100 μm in a volume-based particle size distribution curve measured by a laser diffraction / scattering particle size distribution measurement method, and the cumulative particle size D 50 4μm or more.

[0081] From the perspective of the dispersion stability and good electrical conductivity of carbon nanotubes, the peak value of the small particle diameter side in the range of 0.1 μm or more and 3 μm or less is preferably a particle diameter of 0.5 μm or more. In addition, it is preferably a particle diameter of 2 μm or less, and more preferably a particle diameter of 1.5 μm or less. Although it is uncertain, it is speculated that the peak value of the small particle diameter side comes from multilayer carbon nanotubes. By setting the peak value of the small particle diameter side to the range, a suitable dispersed carbon nanotube dispersion can be obtained. If the peak value of the small particle diameter side exceeds the range, there is a conductive material in a coagulated state. In addition, if it is higher than the range, a plurality of finely broken conductive materials will be produced, so there is a concern that it is difficult to form an efficient conductive network. For example, the small particle diameter side peak value can be a particle diameter of 0.1 μm or more and 3 μm or less, a particle diameter of 0.5 μm or more and 2 μm or less, or a particle diameter of 0.5 μm or more and 1.5 μm or less.

[0082] From the perspective of the dispersion stability and good conductivity of carbon nanotubes, the peak value on the large particle size side in the range of 10 μm or more and 100 μm or less is preferably 15 μm or more, more preferably 20 μm or more. In addition, the particle size is preferably 80 μm or less, more preferably 50 μm or less. Although it is uncertain, it is speculated that the peak value on the large particle size side comes from the single-layer carbon nanotubes. By setting the peak value on the large particle size side to the range, an excellent conductivity and uniform dispersion liquid supporting the single-layer carbon nanotubes can be obtained, and then, even if it is dried due to film making, it will not condense, and a uniformly dispersed state can be maintained in the electrode after drying. For example, the peak value on the large particle size side may be a particle size of 10 μm or more and 100 μm or less, a particle size of 15 μm or more and 80 μm or less, or 20 μm or more and 50 μm or less.

[0083] Cumulative particle size D 50 The cumulative particle size D is 4 μm or more, preferably 8 μm or more, and more preferably 10 μm or more. In addition, it is preferably 100 μm or less, and more preferably 30 μm or less. 50 Within the above range, the carbon nanotubes are in a state of being untied in the dispersion without being broken, and a carbon nanotube dispersion having a long conductive path is obtained. In addition, the viscosity increase caused by the structural viscosity between the carbon nanotubes can be suppressed, and conductivity and stability can be achieved at the same time. 50 The particle size is 4 μm or more, which prevents the carbon nanotubes from being dispersed too finely and causing the structural viscosity between the carbon nanotubes to increase, and the stability over time will not deteriorate. Furthermore, there are sufficiently long conductive paths, and conductivity can be achieved. Cumulative particle size D 50 It may be 4 μm or more and 100 μm or less, 8 μm or more and 50 μm or less, or 10 μm or more and 30 μm or less.

[0084] Laser diffraction / scattering particle size distribution measurement can be obtained by using a laser diffraction / scattering particle size distribution device under the condition that the transmittance of laser light is 60%. The dilution solvent is measured using the same solvent as the solvent in the carbon nanotube dispersion. Specifically, it can be obtained by the method described in the examples.

[0085] The laser diffraction / scattering particle size distribution determination method is a determination method as follows: the particle size distribution is calculated based on information of scattered (diffracted) light from particles when the particles (carbon nanotubes in this specification) are irradiated with laser light, which can be used as an indicator of dispersed particle size and dispersion state. Usually, the scattered light intensity of the particles is proportional to the diameter (circumference) of the particles and inversely proportional to the wavelength of the incident laser. In addition, it depends on the refractive index inherent in the particles. When the particle size is large, the scattered light is concentrated in the front. When the particle size is smaller than the incident wavelength of the laser, the scattered light is scattered in all directions including the side and the back. In addition, these scattered lights are detected by a detector, and a continuous particle size distribution curve with the horizontal axis as the particle size and the vertical axis as the volume-based frequency can be determined through Fourier transform. The light transmittance of the laser is related to the sample concentration during the measurement. The thinner the sample, the greater the transmittance.

[0086] The carbon nanotube dispersion according to some embodiments has at least two particle size distribution peaks in a volume-based particle size distribution curve, and the particle diameter at each particle size distribution peak is the most frequent particle diameter within the peak, also called the most frequent diameter.

[0087] For example, in Figure 1 The particle size distribution curve shown in FIG. 1 has two particle size distribution peaks, one at 0.7 μm in the range of particle size of 0.1 μm or more and 3 μm or less, and the other at 19.9 μm in the range of particle size of 10 μm or more and 100 μm or less. The cumulative particle size D 50 It is 11.1μm.

[0088] The larger the fiber length of the carbon nanotubes in the carbon nanotube dispersion, the more efficiently a conductive network can be formed in a small amount, which can reduce the amount of conductive material required in the battery electrode. However, the cohesive force of carbon nanotubes with large fiber length is strong, and it is difficult to disperse. Furthermore, the carbon nanotubes are easily broken in the dispersion process, and it is also difficult to control the fiber length of the carbon nanotubes. The particle size distribution characteristics of the carbon nanotubes in the carbon nanotube dispersion are as described above, and a plurality of carbon nanotubes can be stably dispersed without agglomeration, which can improve the stability over time. Thus, a conductive network can be formed in a small amount and efficiently, which can reduce the amount of conductive material required in the battery electrode. In addition, dispersibility and stability can be taken into account, and good dispersion can also be maintained in the electrode composite slurry and / or the electrode film.

[0089] As a method for controlling the particle size distribution characteristics of the carbon nanotube dispersion as described above, it can be appropriately adjusted according to the type and amount of the carbon nanotubes used, the type and amount of the dispersant, the type of the solvent or the dispersion conditions, etc. Among them, the case of using a plurality of carbon nanotubes with different fiber diameters, the case of using multilayer carbon nanotubes and single-layer carbon nanotubes as carbon nanotubes, and the case of controlling by adjusting the amount of the carbon nanotubes, the dispersion conditions, etc. are effective for balancing the temporal stability of the carbon nanotube dispersion and the conductivity of the battery, and are therefore preferred.

[0090] [Fiber diameter distribution]

[0091] In the fiber diameter distribution of carbon nanotubes measured by a transmission electron microscope, the carbon nanotube dispersion preferably has at least two fiber diameter distributions in the range of fiber diameters of 0.1 nm or more and 20 nm or less. The fiber diameter distribution is obtained by observing and photographing the carbon nanotubes in the carbon nanotube dispersion by a transmission electron microscope, selecting any 300 carbon nanotubes in the obtained observation photographs, and measuring the fiber diameters of each. In addition, the average fiber diameter (nm) of the carbon nanotubes is calculated based on the number average. Specifically, the fiber diameter distribution and the average fiber diameter can be confirmed by the method described in the examples and by a transmission electron microscope.

[0092] The so-called at least two fiber diameter distributions means that there are at least two peaks in the fiber diameter distribution. Preferably, the two peaks do not overlap. In the case where part of the two peaks overlap, the region with the smallest fiber diameter at the inflection point of the frequency (%) curve of the overlapping portion of the peak is used as the boundary, and the region with a larger fiber diameter than the first fiber diameter distribution (I) is used as the second fiber diameter distribution (II).

[0093] The first fiber diameter distribution (I) is preferably in the range of 0.1 nm or more and less than 5 nm. More preferably, the smallest fiber diameter is 0.5 nm or more, and further preferably, 1 nm or more. In addition, more preferably, the largest fiber diameter is less than 3 nm.

[0094] The second fiber diameter distribution (II) is preferably in the range of 3 nm or more and 20 nm or less. More preferably, the smallest fiber diameter is 5 nm or more. In addition, more preferably, the largest fiber diameter is 10 nm or less.

[0095] For example, it is preferred that the first fiber diameter distribution (I) is 0.5 nm or more and less than 3 nm, and the second fiber diameter distribution (II) is 3 nm or more and 10 nm or less.

[0096] By having the first fiber diameter distribution (I) and the second fiber diameter distribution (II) within the above range, a dispersion in which the carbon nanotubes are uniformly dispersed without forming entangled aggregates can be obtained. In addition, even if the coating is dried, the carbon nanotubes will not aggregate, and a uniformly dispersed state can be maintained in the electrode after drying, thereby improving the output and cycle life of the secondary battery.

[0097] The content of the carbon nanotubes (I) constituting the first fiber diameter distribution (I) is based on the total amount of the carbon nanotubes, and is preferably 10% or more on a number basis, and more preferably 15% or more. In addition, it is preferably 90% or less, more preferably 80% or less, and further preferably 50% or less. In addition, the content of the carbon nanotubes (II) constituting the second fiber diameter distribution (II) is based on the total amount of the carbon nanotubes, and is preferably 5% or more on a number basis, more preferably 25% or more, and further preferably 50% or more. In addition, it is preferably 90% or less, and more preferably 85% or less. By including carbon nanotubes (I) and carbon nanotubes (II) above the lower limit, a carbon nanotube dispersion can be made that can suppress the structural viscosity of the carbon nanotubes and can form short conductive paths and long conductive paths.

[0098] The fiber diameter at the peak of the first fiber diameter distribution (I) is preferably 0.5 nm or more, more preferably 1 nm or more. In addition, it is preferably 3 nm or less, more preferably less than 3 nm, and more preferably 2 nm or less. For example, the fiber diameter at the peak of the first fiber diameter distribution (I) may be 0.5 nm or more and 3 nm or less, 1 nm or more and less than 3 nm, or 1 nm or more and 2 nm or less.

[0099] The fiber diameter at the peak of the second fiber diameter distribution (II) is preferably 5 nm or more. In addition, it is preferably 20 nm or less, and more preferably 15 nm or less. For example, the fiber diameter at the peak of the second fiber diameter distribution (II) may be 5 nm or more and 20 nm or less, 5 nm or more and 15 nm or less, 5 nm or more and 10 nm or less, or 6 nm or more and 8 nm or less.

[0100] For example, the difference between the fiber diameter at the peak of the first fiber diameter distribution (I) and the fiber diameter at the peak of the second fiber diameter distribution (II) may be 1 nm to 15 nm, 2 nm to 10 nm, 3 nm to 8 nm, or 4 nm to 6 nm.

[0101] In the carbon nanotube dispersion of some embodiments, the content of carbon nanotubes with a fiber length of 5.0 μm or less is preferably 90% or less, more preferably 85% or less, and further preferably 75% or less, based on the total amount of carbon nanotubes, based on the number of the carbon nanotubes. In addition, the content of carbon nanotubes with a fiber length greater than 5.0 μm is preferably 5% or more, more preferably 10% or more, and further preferably 15% or more, based on the number of the carbon nanotubes, based on the total amount of the carbon nanotubes.

[0102] When the carbon nanotubes meet the conditions, the carbon nanotubes with different fiber diameter distributions can be dispersed without agglomeration, which can suppress the viscosity increase over time, so that good dispersion can be maintained in the electrode composite slurry and / or the electrode film, so it is preferred. The fiber length of the carbon nanotubes in the carbon nanotube dispersion can be confirmed as follows. First, the carbon nanotubes are observed and photographed using a scanning electron microscope. Secondly, in the observation photo, it can be confirmed by measuring the fiber length of the carbon nanotubes. In addition, the average fiber length is to randomly select 300 carbon nanotubes in the observation photo, measure the fiber length of each, and use its average value as the average fiber length. In addition, in this specification, the fiber length of the carbon nanotube is the fiber length in the carbon nanotube dispersion, that is, the fiber length after preparing the carbon nanotube dispersion.

[0103] [pH]

[0104] The "pH" of the carbon nanotube dispersion in some embodiments refers to the following value, which is prepared by adding water to the carbon nanotube dispersion so that the solid content concentration before adding water is set to 100% and the solid content concentration after adding water becomes 50%, and the value is measured using a conventional pH meter, for example, it can be measured by the following method.

[0105] While stirring a carbon nanotube dispersion having a solid content concentration of 2% by using a disperser or the like, water is added to make the solid content concentration of the carbon nanotube dispersion 1%. After stirring evenly, the pH of the carbon nanotube dispersion can be measured at 25°C using a desktop pH meter (Seven Compact S220 Expert Pro, manufactured by Mettler-Toledo). The pH of the carbon nanotube dispersion is preferably 8 or more. In addition, it is preferably 12 or less, and more preferably 11 or less. By adjusting the pH to within the range, the wettability of CNTs can be improved, and the stability of the dispersion can be improved. If the pH is within the range, it is easy to suppress the corrosion of various raw materials and outer packaging materials in the battery, or the gelation of the adhesive, and so it is preferred. For example, the pH of the carbon nanotube dispersion can be 8 to 12 or 8 to 11. In more detail, the pH of the carbon nanotube dispersion can be 8.0 to 12.0, 8.5 to 11.5, or 7.0 to 11.0.

[0106] The pH of the carbon nanotube dispersion can be adjusted by (1) the amount of metal hydroxide contained in the CNT, (2) the type and amount of functional groups on the surface of the CNT, and (3) the type and amount of the added alkali. By adjusting the pH by combining all the factors (1) to (3), not only the wettability of the CNT can be improved, but also even when a plurality of carbon nanotubes with different dispersivities are used in combination, the dispersants that contribute to the dispersion of each can be stabilized without being mutually coordinated, and a carbon nanotube dispersion having excellent not only dispersibility but also stability can be obtained. In addition, in terms of obtaining a buffering effect corresponding to the pH change during mixing of the active material or binder resin added when manufacturing the composite slurry for the electrode, it is also preferred to adjust the pH of the carbon nanotube dispersion to an appropriate range.

[0107] [Complex elastic modulus and phase angle]

[0108] The dispersibility of the carbon nanotube dispersion of the present embodiment can be evaluated by the complex elastic modulus and phase angle obtained by utilizing dynamic viscoelasticity measurement, and the complex elastic modulus and phase angle can be measured by the method described in the embodiment. The complex elastic modulus of the carbon nanotube dispersion represents the hardness of the carbon nanotube dispersion, and the better the dispersibility of the carbon nanotubes, and the lower the viscosity of the carbon nanotube dispersion composition, the smaller the tendency of the dispersion. However, in the case of a large fiber length of the carbon nanotube, even if the carbon nanotube is uniformly and stably untied in the medium, due to the structural viscosity of the carbon nanotube itself, the complex elastic modulus sometimes also becomes a high value. In addition, in addition to the dispersion state of the carbon nanotube, it also changes due to the entanglement of the carbon nanotube, the dispersant and other resin components, or the influence of their intermolecular forces, etc. In addition, the phase angle refers to the phase shift of the stress wave when the strain applied to the carbon nanotube dispersion is set to a sine wave. If it is a pure elastic body, it becomes a sine wave with the same phase as the applied strain, so the phase angle becomes 0 °. On the other hand, if it is a pure viscous body, it becomes a stress wave that advances 90°. In the usual viscoelasticity measurement sample, the phase angle becomes a sine wave greater than 0° and less than 90°. If the dispersibility of the carbon nanotubes in the carbon nanotube dispersion is good, the phase angle is close to 90° as a pure viscous body. However, like the complex elastic modulus, in the case of the structural viscosity of the conductive material itself, even if the conductive material is uniformly and stably untied in the dispersion medium, the phase angle sometimes becomes a low value. In addition, like the complex elastic modulus, in addition to the dispersion state of the carbon nanotubes, it also changes due to the entanglement of the carbon nanotubes, dispersants and other resin components, or the influence of their intermolecular forces.

[0109] The carbon nanotube dispersion of this embodiment controls the particle size distribution characteristics of the carbon nanotubes in the dispersion within a specific range of conditions, and suppresses the aggregation of multiple carbon nanotubes by highly controlling the hardness, structure and viscosity of the dispersion regarding the relationship between the fiber diameter and fiber length of such carbon nanotubes, so that the carbon nanotube dispersion has excellent time stability. Furthermore, when the carbon nanotube dispersion is used to prepare a composite material slurry for an electrode and to manufacture an electrode film, it can also maintain its good dispersion state and form a good conductive network in the electrode.

[0110] The complex elastic modulus of the carbon nanotube dispersion of the present embodiment using dynamic viscoelasticity is preferably 5 Pa to 800 Pa, more preferably 5 Pa to 400 Pa.

[0111] The phase angle of the carbon nanotube dispersion liquid of the present embodiment is preferably 3° to 50°, more preferably 7° to 50°.

[0112] Furthermore, when the complex elastic modulus X (Pa) and the phase angle Y (°) are within the preferred ranges and their product (X×Y) is 15 or more and 5,000 or less, an electrode film having high fluidity and very good conductivity can be obtained.

[0113] The amount of the carbon nanotubes in the carbon nanotube dispersion of the present embodiment is preferably 0.4 to 5.0 parts by mass, more preferably 0.4 to 3.0 parts by mass, based on 100 parts by mass of the carbon nanotube dispersion.

[0114] The viscosity of the carbon nanotube dispersion of the present embodiment, as measured at 60 rpm using a Brookfield viscometer, is preferably 10,000 mPa·s or less, more preferably 6,000 mPa·s or less, and still more preferably 3,000 mPa·s or less.

[0115] 《Composite material slurry for electrode》

[0116] The electrode composite material slurry contains a carbon nanotube dispersion and a positive electrode active material or a negative electrode active material. It may further contain a binder resin, or other conductive materials, a solvent, and may further mix any components. In this specification, the positive electrode active material and the negative electrode active material are sometimes referred to as "active materials". The so-called active material refers to the material that forms the basis of the battery reaction. The active material is divided into a positive electrode active material and a negative electrode active material according to the electromotive force. In this specification, the electrode composite material slurry containing the positive electrode active material or the negative electrode active material is sometimes referred to as "positive electrode slurry", "negative electrode slurry", "composite material slurry" or simply "electrode slurry". In order to improve uniformity and processability, the electrode composite material slurry is preferably in a slurry state.

[0117] <Positive electrode active material>

[0118] The positive electrode active material is not particularly limited. For example, in secondary battery applications, metal compounds such as metal oxides and metal sulfides that can be reversibly doped or embedded with lithium ions can be used. Examples include lithium manganese composite oxides (e.g., Li x Mn2O4 or Li x MnO2), lithium nickel composite oxides (such as Li x NiO2), lithium cobalt composite oxide (Li x CoO2), lithium nickel cobalt composite oxide (such as Li x Ni 1-y Co y O2), lithium manganese cobalt composite oxide (such as Li x Mn y Co 1-y O2), lithium nickel manganese cobalt composite oxide (such as Li x Ni y Co z Mn 1-y-z O2), spinel lithium manganese nickel composite oxide (such as Li x Mn 2-y Ni y O4) and other lithium and transition metal composite oxide powders, lithium phosphate powders with olivine structure (such as Li x FePO4、Li x Fe 1-y Mn y PO4、Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxide (such as V2O5, V6O 13 ), transition metal oxide powders such as titanium oxide, transition metal sulfide powders such as iron sulfate (Fe2(SO4)3), TiS2, and FeS, etc. Among them, x, y, z are quantities, 0<x<1, 0<y<1, 0<z<1, 0<y+z<1. These positive electrode active materials can also be used alone or in combination. Among these active materials, especially active materials containing Ni and / or Mn (special cases where the total amount of Ni and / or Mn in the transition metal is 50 mol% or more), due to the dissolution of raw material source components or metal ions, there is a tendency for alkalinity to become higher, and due to its influence, it is easy to cause gelation of the binder or deterioration of the dispersion state, so the problem of the present invention is significantly manifested. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, the present invention is particularly effective.

[0119] <Negative electrode active material>

[0120] The negative electrode active material is not particularly limited, and for example, metal Li, or its alloys, tin alloys, silicon alloy negative electrodes, Li x TiO2、Li x Fe2O3、Li x Fe3O4、Li x Metal oxides such as WO2, conductive polymers such as polyacetylene and polyparaphenylene, artificial graphites such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials. Wherein, x is the number, 0<x<1. These negative electrode active materials can also be used alone or in combination. In particular, when a silicon alloy negative electrode is used, the theoretical capacity is large, and on the other hand, the volume expansion is extremely large, so it is preferably used in combination with artificial graphites such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials.

[0121] Based on the mass of the active material (the mass of the active material is set to 100 mass%), the content of CNT in the electrode composite material slurry is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and further preferably 0.10% or more. In addition, it is preferably 10 mass% or less, more preferably 5 mass% or less, and further preferably 3 mass% or less. In addition, in the case of further including carbon black as a conductive material, based on the mass of the active material (the mass of the active material is set to 100 mass%), the content of carbon black is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and further preferably 1% or more. In addition, it is preferably 20 mass% or less, more preferably 10 mass% or less. In the case of using carbon nanotubes and carbon black as conductive materials, it is preferred that the total amount of each added is within the range. If it is higher than the range, the filling amount of the active material in the electrode is reduced, resulting in low battery usage. In addition, if it is lower than the range, the conductivity of the electrode and the battery is sometimes insufficient.

[0122] Based on the mass of the active material (the mass of the active material is set to 100 mass%), the content of the dispersant in the electrode composite material slurry is preferably 0.01 mass% or more, more preferably 0.02 mass% or more. In addition, it is preferably 10 mass% or less, more preferably 5 mass% or less.

[0123] <Binder resin>

[0124] In the case where the composite material slurry for electrode further includes a binder resin, there is usually no particular restriction as long as it is a binder resin used as a binder resin for coating, and it can be appropriately selected according to the purpose. In addition, the binder resin used in the composite material slurry for electrode is a resin that can bind active materials, conductive materials and other substances. The binder resin used in the composite material slurry for electrode can be listed, for example: polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylate, methacrylic acid, methacrylate, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as constituent units; polyurethane resin, polyester resin, phenol resin, epoxy resin, phenoxy resin, urea resin, melamine resin, alkyd resin, acrylic resin, formaldehyde resin, silicone resin, fluororesin; cellulose resin; elastomers such as styrene-butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene, etc. In addition, it can also be a modified substance or mixture of these resins, and a copolymer. Among these, when used as a binder resin for the positive electrode, in terms of resistance, it is preferred to use the fluorine-based resin, such as polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, etc. as the binder resin. In addition, when used as a binder resin for the negative electrode, it is preferred to use carboxymethyl cellulose (CMC), styrene butadiene rubber, polyacrylic acid, etc., which have good adhesion.

[0125] When the electrode composite material slurry contains a binder resin, the content of the binder resin in the electrode composite material slurry is preferably 0.5% by mass or more, more preferably 0.5% by mass or more, based on the mass of the active material (the mass of the active material is set to 100% by mass). In addition, it is preferably 30% by mass or less, more preferably 25% by mass or less, and further preferably 20% by mass or less.

[0126] Based on the mass of the composite material slurry for electrode (the mass of the composite material slurry for electrode is set to 100 mass%), the solid content in the composite material slurry for electrode is preferably 30 mass% or more, more preferably 40 mass% or more. In addition, it is preferably 90 mass% or less, more preferably 80 mass% or less.

[0127] The composite material slurry for the electrode can be prepared by various methods known in the past, such as: a method of adding an active material to a carbon nanotube dispersion; a method of adding an active material to the carbon nanotube dispersion and then adding a binder resin; a method of adding a binder resin to the carbon nanotube dispersion and then adding an active material.

[0128] The dispersing device used for dispersing is not particularly limited. The dispersing mechanism listed in the description of the carbon nanotube dispersion can be used to obtain the electrode composite material slurry. Therefore, as a method for making the electrode composite material slurry, a process of adding an electrode active material and dispersing it instead of adding a binder resin to the carbon nanotube dispersion can be performed.

[0129] <Electrode film>

[0130] The electrode film includes at least one selected from the group consisting of a film formed using a carbon nanotube dispersion and a film formed using an electrode composite material slurry. The electrode film may also include a current collector. The electrode film can be obtained, for example, by applying an electrode composite material slurry on the current collector and drying it, and includes a current collector and a film. The electrode film formed using a positive electrode composite material composition can be used as a positive electrode. The electrode film formed using a negative electrode composite material composition can be used as a negative electrode. In this specification, a film formed using an electrode composite material slurry containing an active material is sometimes referred to as an "electrode composite material layer".

[0131] The material and shape of the current collector used in the formation of the electrode film are not particularly limited, and the material and shape suitable for various secondary batteries can be appropriately selected. As the material of the current collector, conductive metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel can be listed. In addition, as the shape, a flat foil can generally be used, but a current collector with a roughened surface, a perforated foil-shaped current collector, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 μm to 30 μm.

[0132] As a method for coating a carbon nanotube dispersion or a composite material slurry for an electrode on a current collector, there is no particular limitation, and known methods can be used. Specifically, die coating, dip coating, roll coating, blade coating, spray coating, gravure coating, screen printing, or electrostatic coating can be cited. As a drying method, natural drying or drying using an air drying machine, a warm air drying machine, an infrared heater, a far infrared heater, etc. can be cited, but it is not particularly limited to these.

[0133] After coating, the coating may be subjected to a calendering treatment using a planographic press, a calender roll, etc. The thickness of the formed film is, for example, 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0134] The film formed using the carbon nanotube dispersion or the electrode composite material slurry can also be used as a base layer of the electrode composite material layer to improve the adhesion between the electrode composite material layer and the current collector or to improve the conductivity of the electrode film.

[0135] <Secondary battery>

[0136] The secondary battery includes a positive electrode, a negative electrode and an electrolyte, and at least one selected from the group consisting of the positive electrode and the negative electrode includes an electrode film.

[0137] As an electrolyte, various electrolytes known in the past in which ions can move can be used. For example, LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is phenyl) and other electrolytes containing lithium salts can be listed, but are not limited to these. The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolyte.

[0138] The non-aqueous solvent is not particularly limited, and examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octalactone; glyme such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and cyclopentane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0139] The non-aqueous electrolyte secondary battery preferably includes a separator. Examples of the separator include polyethylene non-woven fabric, polypropylene non-woven fabric, polyamide non-woven fabric, and non-woven fabrics obtained by subjecting these non-woven fabrics to hydrophilic treatment, but the separator is not particularly limited to these.

[0140] The structure of the nonaqueous electrolyte secondary battery of this embodiment is not particularly limited, and generally includes a positive electrode and a negative electrode, and a separator provided as required, and can be configured in various shapes such as paper type, cylindrical type, button type, and stacked type according to the purpose of use.

[0141] Example

[0142] The present invention is described in more detail below with reference to the following examples. The present invention is not limited to the following examples unless it exceeds the gist thereof. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". In addition, carbon nanotubes are sometimes referred to as "CNTs".

[0143] <Average fiber diameter of carbon nanotubes>

[0144] The average fiber diameter of carbon nanotubes can be calculated by forming a film using a diluted solution of carbon nanotubes and observing it using a direct transmission electron microscope (H-7650, manufactured by Hitachi, Ltd.) at a magnification of 50,000 times. The fiber diameters of 300 randomly extracted carbon nanotubes are measured and calculated based on the average value.

[0145] <Laser diffraction / scattering particle size distribution measurement of carbon nanotube dispersion>

[0146] The particle size distribution is measured using a laser diffraction / scattering particle size distribution measuring device (manufactured by Horiba, Ltd., Partical LA-960V2). The laser wavelength of this measuring device is 650nm, and as detectors, it includes 1 annular 64-segment silicon photodiode, 5 four-channel (4ch) array detectors, and 3 silicon photodetectors. In addition, the measuring unit uses a flow cell (sample cell) made of synthetic quartz. First, NMP, which is the same solvent as the dispersion liquid, is added to the sample bath including the sample cell, and circulation / ultrasonic cleaning is performed. As the action mode, it is set to circulation speed: 3, ultrasonic intensity: 7, ultrasonic time 1 minute, stirring speed: 7, stirring mode: continuous. Then, in order to exhaust, ultrasonic action is performed under the conditions of ultrasonic intensity of 7 and ultrasonic time of 5 seconds, and then a blank (background) measurement is performed. The particle size reference is set to volume, the particle refractive index is set to 1.920-0.522i (carbon material), and the solvent refractive index is set to 1.468 (NMP). The dispersion liquid is added dropwise so that the laser transmittance during measurement is 60% ± 1%, and the sample is adjusted. The measurement is performed with the action mode set to cycle speed: 3, stirring speed: 7, stirring mode: continuous. For example, Figure 1 It is a graph showing the distribution diagram of the frequency of the particle size of the carbon nanotube dispersion 1. The left vertical axis represents the frequency (%) relative to the whole, and the right vertical axis corresponds to the cumulative frequency.

[0147] <CNT fiber diameter of carbon nanotube dispersion>

[0148] The carbon nanotube dispersion was appropriately diluted, and a few μL was dripped onto the collodion film. After drying at room temperature, it was observed using a direct transmission electron microscope (H-7650, manufactured by Hitachi, Ltd.). The observation was performed at a magnification of 50,000 times, and multiple photos containing more than 10 CNTs in the field of view were taken. The fiber diameters of 300 randomly selected carbon nanotubes were measured. For the fiber diameters of the 300 randomly selected carbon nanotubes, the frequency (%) based on the number was taken as the vertical axis, and the fiber diameter (nm) was taken as the horizontal axis to plot and confirm the fiber diameter distribution. For example, Figure 2It is a graph showing the distribution of the fiber diameters of the carbon nanotube dispersion 1, and the frequency (%) on the vertical axis corresponds to the "content ratio based on the number of carbon nanotubes relative to the total amount of carbon nanotubes".

[0149] <pH of Carbon Nanotube Dispersion Liquid>

[0150] After the carbon nanotube dispersion was allowed to stand in a thermostatic bath at 25°C for more than 1 hour, the carbon nanotube dispersion was stirred sufficiently to set the solid content concentration of the carbon nanotube dispersion to 100%, and water was added to the carbon nanotube dispersion while stirring using a disperser to set the solid content concentration to 50%. After stirring uniformly, the pH was measured at 25°C using a tabletop pH meter (Seven Compact S220Expert Pro, manufactured by Mettler-Toledo).

[0151] The details of the materials used in this example are as follows.

[0152] <Carbon Nanotube>

[0153] CNT (1-1): TUBALL 01RW03 (manufactured by OCSiAl, single-walled carbon nanotube)

[0154] CNT (1-2): TUBALL 01RW02 (manufactured by OCSiAl, single-walled carbon nanotube)

[0155] CNT (1-3): TNSAR (manufactured by Timesnano, single-walled carbon nanotube)

[0156] CNT (2-1): JENOTUBE 6A (manufactured by JEIO, multi-walled carbon nanotube)

[0157] CNT (2-2): JENOTUBE 10B (manufactured by JEIO, multi-walled carbon nanotube)

[0158] CNT (2-3): CNT (2-1) subjected to the following purification treatment

[0159] CNT (2-4): CNT (2-2) subjected to the following purification treatment

[0160] ·CNT (3-1): VGCF (manufactured by Showa Denko Co., Ltd., carbon nanofiber)

[0161] (Production of CNT (2-3): Carbon Nanotube Purification Process)

[0162] 10 kg of CNT (2-1) (manufactured by JEIO, JENOTUBE 6A) is measured in a 120 L heat-resistant container, and the heat-resistant container with CNT is placed in a furnace. Then, nitrogen is introduced into the furnace, and the air in the furnace is exhausted while maintaining a positive pressure. After the oxygen concentration in the furnace reaches less than 0.1%, it is heated to 1500°C over 30 hours. While maintaining the temperature in the furnace at 1500°C, chlorine is introduced at a rate of 50 L / min for 100 hours. Then, nitrogen is introduced at 50 L / min, and cooled while maintaining a positive pressure to obtain CNT (2-3).

[0163] (Production of CNT (2-4): Carbon Nanotube Purification Process)

[0164] CNT (2-4) was obtained in the same manner as in the production of CNT (2-3) except that CNT (2-1) was replaced by CNT (2-2).

[0165] The average fiber diameter of CNT [nm] and Brunauer-Emmett-Teller (BET) specific surface area [m 2 / g] is shown below.

[0166] [Table 1]

[0167] Table 1.

[0168]

[0169] <Dispersant>

[0170] Dispersant (B-1): Therban (R) 4307 (manufactured by ARLANXEO Co., Ltd., hydrogenated acrylonitrile rubber, acrylonitrile content 43.0%)

[0171] Dispersant (B-2): Zetpole (R) 3300 (manufactured by Zeon Co., Ltd., Japan, hydrogenated acrylonitrile rubber, acrylonitrile content 23%)

[0172] Dispersant (B-3): polyvinyl pyrrolidone (manufactured by Nippon Catalyst Co., Ltd., K-30, weight average molecular weight 40,000)

[0173] Dispersant (B-4): polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., BL-10, calculated molecular weight 15,000)

[0174] Dispersant (B-5): PVDF: polyvinylidene fluoride (Solef #5130 (manufactured by Solvey Co., Ltd.), solid content 100%)

[0175] <Additives>

[0176] ·NaOH; sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., reagent premium grade)

[0177] KOH; Potassium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., reagent premium grade)

[0178] 2-aminoethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., Wako Grade 1)

[0179] (Production Example 1: Preparation of Carbon Nanotube Pre-dispersion Liquid 1)

[0180] According to the composition shown in Table 2, 2 parts of dispersant (B-1) and 97.6 parts of NMP (N-methyl-2-pyrrolidone) were added to a stainless steel container and stirred until uniform using a disperser. Then, 0.4 parts of CNT (1-1) were added while stirring with a disperser, and a square hole high shear screen was installed in a high shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed at a speed of 8,500 rpm until the whole became uniform. Next, the contents of the stainless steel container were liquid-sent and passed through a bead mill filled with zirconia beads with a diameter of 1.0 mm φ (Dyno-MILL Multifunctional Laboratory (MULTILAB), manufactured by Shinmaru Enterprises), and a circulatory dispersion treatment with a residence time of 10 minutes was performed. Then, the dispersion was supplied from the stainless steel container to a high-pressure homogenizer (Star Burst Labo HJP-17007, manufactured by SUGINO MACHINE) via a pipe, and the dispersion was passed through 20 times to obtain a carbon nanotube pre-dispersion liquid 1. The dispersion was carried out using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa.

[0181] (Production Examples 2 to 4, 6 to 16: Carbon Nanotube Preliminary Dispersion Liquids 2 to 4, 6 to 16)

[0182] Dispersions (carbon nanotube pre-dispersions 2 to 16) were obtained in the same manner as in Preparation Example 1 according to the compositions shown in Table 2. In Preparation Examples 13 to 15, dispersions were prepared in the same manner as in Example 1 except that the bases shown in Table 2 were added as additives together with the dispersant.

[0183] (Production Example 5: Carbon Nanotube Pre-dispersion Liquid 5)

[0184] According to the composition shown in Table 2, 2 parts of dispersant (B-1) and 97.6 parts of NMP were added to a stainless steel container and stirred until uniform by a disperser. Then, 0.4 parts of CNT (1-1) were added while stirring with a disperser, and a square hole high shear screen was installed in a high shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed at a speed of 8,500 rpm until the whole became uniform. Next, the contents of the stainless steel container were liquid-sent and passed through a bead mill filled with zirconia beads with a diameter of 1.0 mm φ (Dyno-MILL Multilab, manufactured by SHINMARU ENTERPRISES) for a circulatory dispersion treatment with a residence time of 30 minutes. Then, the dispersed liquid was supplied from the stainless steel container via a pipe to a high pressure homogenizer (Star Burst Labo HJP-17007, manufactured by SUGINO MACHINE) and dispersed 20 times. The dispersion was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa.

[0185] [Table 2]

[0186] Table 2.

[0187]

[0188] (Example A-1)

[0189] The carbon nanotube pre-dispersion liquid 1 and the carbon nanotube pre-dispersion liquid 6 prepared in Production Example 1 were weighed into a stainless steel container so as to give a CNT mass ratio of 1:5. Then, the mixture was stirred with a disperser until it became uniform, thereby obtaining a carbon nanotube dispersion liquid 1.

[0190] (Examples A-2 to A-17, Comparative Examples A-1 to A-3)

[0191] Except having changed into the composition and the blending amount (mass parts) shown in Table 2, it carried out similarly to Example A-1, and obtained each carbon nanotube dispersion liquid (carbon nanotube dispersion liquid 2-17, 20-22).

[0192] (Example A-18)

[0193] 1.20 parts of dispersant (B-1) and 97.84 parts of NMP were added to a stainless steel container and stirred until uniform using a disperser. Then, 0.80 parts of CNT (2-1) were measured, added while stirring with a disperser, and a square hole high shear screen was installed in a high shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed at a speed of 8,600 rpm until the whole became uniform. Then, it was supplied from the stainless steel container via a pipe to a high pressure homogenizer (Star Burst Labo HJP-17007, manufactured by SUGINO MACHINE), and 20 passes were made for dispersion treatment, and then 0.16 parts of CNT (1-1) were supplied to the high pressure homogenizer, and 10 passes were made for dispersion treatment, thereby obtaining a carbon nanotube dispersion 20. The dispersion treatment was performed using a single nozzle chamber at a nozzle diameter of 0.25 mm and a pressure of 100 MPa.

[0194] (Example A-19)

[0195] 0.40 parts of dispersant (B-1) and 47.84 parts of NMP were added to a stainless steel container, and stirred with a disperser until uniform. Then, 0.80 parts of CNT (2-1) were measured, added while stirring with a disperser, and a square hole high shear screen was installed in a high shear mixer (L5M-A, manufactured by SILVERSON), and dispersed in batches at a speed of 8,600 rpm until the whole became uniform, and a carbon nanotube pre-dispersion liquid 21a was obtained. In addition, 0.80 parts of dispersant (B-5) and 50.00 parts of NMP were added to a stainless steel container, and stirred with a disperser until it became uniform. Then, 0.16 parts of CNT (1-1) were measured, added while stirring with a disperser, and a square hole high shear screen was installed in a high shear mixer (L5M-A, manufactured by SILVERSON), and dispersed in batches at a speed of 8,600 rpm until the whole became uniform, and a carbon nanotube pre-dispersion liquid 21b was obtained.

[0196] Then, the carbon nanotube pre-dispersion liquid 21a was supplied from the stainless steel container to a high-pressure homogenizer (Star Burst Labo HJP-17007, manufactured by SUGINO MACHINE) via a pipe and subjected to 20 passes of dispersion treatment, and then the carbon nanotube pre-dispersion liquid 21b was supplied to the high-pressure homogenizer via a pipe and further subjected to 10 passes of dispersion treatment, thereby obtaining a carbon nanotube dispersion liquid 21. The dispersion treatment was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa.

[0197]

[0198] 《Physical properties and evaluation of carbon nanotube dispersions》

[0199] The particle size distribution of the carbon nanotube dispersion, the carbon nanotube fiber diameter, pH, initial and aging (40° C., 3 days later), complex elastic modulus, and phase angle were evaluated by the following methods.

[0200] <Measurement of initial and time-dependent viscosity of carbon nanotube dispersion>

[0201] The viscosity value was measured using a B-type viscometer ("BL" manufactured by Toki Sangyo Co., Ltd.), and the carbon nanotube dispersion was allowed to stand in a constant temperature bath at 25°C for more than 1 hour, and then the measurement was performed at a B-type viscometer rotor speed of 60 rpm. Regarding the type of rotor used in the measurement, when the viscosity value was less than 100 mPa·s, a No. 1 rotor was used, when the viscosity value was 100 mPa·s or more and less than 500 mPa·s, a No. 2 rotor was used, when the viscosity value was 500 mPa·s or more and less than 2,000 mPa·s, a No. 3 rotor was used, and when the viscosity value was 2,000 mPa·s or more and less than 10,000 mPa·s, a No. 4 rotor was used. The lower the viscosity, the better the dispersibility, and the higher the viscosity, the worse the dispersibility. If the obtained carbon nanotube dispersion is obviously separated or precipitated, it is judged to be poorly dispersible.

[0202] Judgment Criteria

[0203] ◎: Less than 3,000 mPa·s (excellent)

[0204] ○: 3,000 mPa·s or more and less than 6,000 mPa·s (good)

[0205] △: 6,000mPa·s or more and less than 10,000mPa·s (acceptable)

[0206] ×: 10,000 mPa·s or more, sedimentation or separation (poor)

[0207] <Measurement of initial and time-dependent complex elastic modulus and phase angle of carbon nanotube dispersion>

[0208] The complex elastic modulus X and phase angle Y of the carbon nanotube dispersion are evaluated in the following manner: using a cone with a diameter of 60 mm and 2°, using a rheometer (RheoStress 1 rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.), at 25°C and a frequency of 1 Hz, a dynamic viscoelasticity measurement is performed with a strain rate in the range of 0.01% to 5%. The smaller the complex elastic modulus obtained, the better the dispersibility, and the larger the dispersibility, the worse the dispersibility. In addition, the larger the phase angle obtained, the better the dispersibility, and the smaller the phase angle obtained, the worse the dispersibility.

[0209] Determination criteria of complex elastic modulus

[0210] ○: 5Pa or more and less than 400Pa (good)

[0211] △: 400Pa or more and 800Pa or less (acceptable)

[0212] ×: Less than 5Pa or more than 800Pa (not allowed)

[0213] Phase angle determination criteria

[0214] ○: 7° or more and less than 50° (good)

[0215] △: 3° or more and less than 7° (acceptable)

[0216] ×: Less than 3° or more than 50° (not allowed)

[0217] [Table 4]

[0218] Table 4.

[0219]

[0220] [Table 5]

[0221] Table 5.

[0222]

[0223] As shown in Table 5, it was confirmed that the initial viscosity, dispersibility and stability after the passage of time of the carbon nanotube dispersions 1 to 19 of the examples were very excellent. On the other hand, the carbon nanotube dispersions 20 to 22 of the comparative examples were high in viscosity and increased in viscosity over time.

[0224] (Example B-1)

[0225] After adding a carbon nanotube dispersion (CNT dispersion 1) and NMP in which 8% by mass PVDF (polyvinylidene fluoride, Solef #5130 (manufactured by Solvey Co., Ltd.) was dissolved as a binder to a 150 mL plastic container, stirring was performed at 2,000 rpm for 30 seconds using an autogenous mixer and an orbital mixer (Are-310, Defoaming Stirring Taro manufactured by Thinky Co., Ltd.) to obtain a carbon nanotube dispersion composition. Subsequently, NMC (NCM523 (manufactured by Nippon Chemical Industry Co., Ltd., composition: LiNi 0.5 Co 0.2 Mn 0.3 O2)) as an electrode active material, using a rotary mixer and a revolution mixer, stirring at 2,000 rpm for 20 minutes. Then, NMP is further added, using a rotary mixer and a revolution mixer, stirring at 2,000 rpm for 30 seconds to obtain an electrode composite slurry. The solid content of the electrode composite slurry is set to 70% by mass. In the non-volatile component of the electrode composite slurry, the non-volatile component ratio of the electrode active material: CNT: binder is set to 98:0.5:1.5.

[0226] The composite material slurry for the electrode was applied onto a 20 μm thick aluminum foil as a current collector using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to adjust the unit area weight of the electrode to 20 mg / cm 2 Then, a roller press (manufactured by Thank-Metal Co., Ltd., 3t hydraulic roller press) was used for rolling treatment to produce a sheet with a density of 3.0g / cm 3 The positive electrode 1 of the electrode film 1.

[0227] <Preparation of composite material slurry for standard negative electrode>

[0228] After adding DENKA Black Li-400 (manufactured by DENKA Co., Ltd.), CMC#1190 (manufactured by Daicel Finechem Co., Ltd.) and water to a plastic container with a capacity of 150 mL, stir at 2,000 rpm for 30 seconds using an autogenous mixer and an orbital mixer (Aerator Taro, ARE-310 manufactured by Thinky Co., Ltd.). Furthermore, artificial graphite CGB-20 (manufactured by Nippon Graphite Industries Co., Ltd.) is added as a negative electrode active material, and stirred at 2,000 rpm for 150 seconds using an autogenous mixer and an orbital mixer. Subsequently, SBR (styrene butadiene rubber, TRD2001 (manufactured by JSR Co., Ltd., solid content 48%)) is added, and stirred at 2,000 rpm for 30 seconds using an autogenous mixer and an orbital mixer to obtain a standard negative electrode composite slurry. The solid content of the standard negative electrode composite slurry is set to 48% by mass. The solid content ratio of negative electrode active material: conductive material: CMC: SBR in the standard negative electrode composite material slurry was set to 97:0.5:1:1.5.

[0229] <Production of standard negative electrode>

[0230] The negative electrode composite material slurry was applied onto a 20 μm thick copper foil as a current collector using an applicator, and then dried in an electric oven at 80°C ± 5°C for 25 minutes to obtain a unit area weight of 10 mg / cm 2 Then, the negative electrode composite material layer was subjected to rolling treatment using a roller press (manufactured by Thank-Metal Co., Ltd., a 3 t hydraulic roller press) to obtain a negative electrode composite material layer with a density of 1.5 g / cm 3 of the negative electrode.

[0231] <Production of Battery 1>

[0232] The standard negative electrode and the obtained positive electrode 1 were punched into 50mm×45mm and 45mm×40mm, respectively, and the separator (porous polypropylene film) to be inserted therebetween was inserted into an aluminum laminate bag, and dried in an electric oven at 70°C for 1 hour. Then, 2mL of electrolyte was injected into a glove box filled with argon, and the aluminum laminate bag was sealed to make a secondary battery 1. The electrolyte was a non-aqueous electrolyte as follows, that is, a mixed solvent of ethylene carbonate, dimethyl carbonate and diethyl carbonate was prepared in a ratio of 1:1:1 (volume ratio), and 1 part of vinylene carbonate (VC) was added as an additive to 100 parts of the electrolyte, and LiPF6 was dissolved at a concentration of 1M to form a non-aqueous electrolyte.

[0233] (Examples B-2 to 19, Comparative Examples B-1 to 3)

[0234] Except for changing to the CNT dispersion shown in Table 6, an electrode film composite material slurry, an electrode film, a positive electrode and a secondary battery were prepared in the same procedure as in Example B-1.

[0235] 《Evaluation of Secondary Batteries》

[0236] The rate characteristics and cycle characteristics of the secondary battery were evaluated by the following methods.

[0237] <Evaluation of rate characteristics of lithium-ion secondary batteries>

[0238] The laminated lithium-ion secondary battery was placed in a constant temperature room at 25°C, and a charge and discharge device (manufactured by Hokuto Electric Co., Ltd., SM-8) was used for charge and discharge measurement. After constant current and constant voltage charging (cut-off current 1.0mA (0.02C)) at a charge end voltage of 4.2V at a charging current of 10mA (0.2C), constant current discharge was performed at a discharge current of 10mA (0.2C) with a discharge end voltage of 2.5V. After repeating the operation three times, constant current and constant voltage charging (cut-off current (1.0mA and 0.02C)) was performed at a charge current of 10mA (0.2C) with a charge end voltage of 4.2V, and constant current discharge was performed at a discharge current of 0.2C and a discharge current of 3C until the discharge end voltage reached 2.5V, and the discharge capacity was calculated respectively. The rate characteristics can be expressed by the following formula based on the ratio of the 0.2C discharge capacity to the 3C discharge capacity.

[0239] (Formula) Rate characteristics = 3C discharge capacity / third 0.2C discharge capacity × 100 (%)

[0240] [Evaluation criteria]

[0241] ◎: Rate characteristics are 80% or more (excellent)

[0242] ○: Rate characteristics are 70% or more and less than 80% (good)

[0243] △: Rate characteristic is 60% or more and less than 70% (acceptable)

[0244] ×: Rate characteristic is less than 60% (not allowed)

[0245] <Evaluation of cycle characteristics of lithium-ion secondary batteries>

[0246] The laminated lithium-ion secondary battery was placed in a constant temperature room at 25°C, and a charge and discharge device (manufactured by Hokuto Electric Co., Ltd., SM-8) was used for charge and discharge measurements. At a charging current of 50mA (1C), constant current and constant voltage charging was performed with a charge termination voltage of 4.2V (cut-off current 1.25mA (0.025C)), and constant current discharge was performed at a discharge current of 50mA (1C) with a discharge termination voltage of 2.5V. The above operation was repeated 200 times. 1C is set as the current value at which the theoretical capacity of the positive electrode is discharged within 1 hour. The cycle characteristics can be expressed by the ratio of the third 1C discharge capacity to the 200th 1C discharge capacity at 25°C, and using the following formula.

[0247] (Formula) Cycle characteristics = 1C discharge capacity at the third time / 1C discharge capacity at the 200th time × 100 (%)

[0248] [Evaluation criteria]

[0249] ◎: Cycle characteristics are 80% or more (excellent)

[0250] ○: Cycle characteristics are 70% or more and less than 80% (good)

[0251] △: Cycle characteristics are 60% or more and less than 70% (acceptable)

[0252] ×: Cycle characteristics less than 60% (unacceptable)

[0253] [Table 6]

[0254] Table 6.

[0255]

[0256] As shown in Table 6, the rate characteristics and cycle characteristics of the battery including the carbon nanotube dispersion having excellent dispersibility, good viscosity and good stability in the positive electrode film are good, and any characteristics of the battery including the carbon nanotube dispersion having poor viscosity in the positive electrode film are poor. If the viscosity is good, a conductive path is uniformly formed in the positive electrode film, so it is inferred that the rate characteristics are improved. In addition, since the load of the cycle is concentrated on the electrode active material particles with lower resistance, it will accelerate the deterioration. In contrast, when a good conductive network is formed as a whole, the load is dispersed, so it is inferred that it is not easy to deteriorate.

[0257] As described above, it can be confirmed that by preparing a carbon nanotube dispersion having a specific particle size distribution characteristic, the conductivity is not impaired even when a plurality of carbon nanotubes are included, and the stability over time is excellent. Among them, when a carbon nanotube dispersion containing two specific carbon nanotubes at a specific mass ratio is used, the characteristics of the two carbon nanotubes can be drawn out to the maximum extent, a good dispersion state is maintained in the electrode film, and an efficient conductive network is formed, and a battery with particularly good rate characteristics and cycle characteristics can be manufactured.

[0258] Although the present invention has been described with reference to the above embodiments, the present invention is not limited to the above contents. Various changes that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention.

[0259] Although the present invention has been described with reference to the above-described embodiments, the present invention is not limited to the above-described embodiments. The structure and details of the present invention can be variously modified within the scope of the present invention.

[0260] The disclosure of the present application is related to the subject matter described in Japanese Patent Application No. 2022-099875 filed on June 21, 2022, and all the disclosed contents are incorporated herein by reference.

[0261] Explanation of symbols

[0262] 1: Particle size distribution peak 1

[0263] 2: Particle size distribution peak 2

Claims

1. A carbon nanotube dispersion comprising carbon nanotubes, a dispersant, and a solvent. In the volume-based particle size distribution curve measured by the laser diffraction / scattering particle size distribution measurement method, The particle size distribution has a peak in the range of a particle size of 0.1 μm or more and 3 μm or less, and in the range of a particle size of 10 μm or more and 100 μm or less, Cumulative particle size D 50 4μm or more.

2. The carbon nanotube dispersion according to claim 1, wherein In the fiber diameter distribution of the carbon nanotube measured by a transmission electron microscope, there are at least two fiber diameter distributions in the range of the fiber diameter being 0.1 nm or more and 20 nm or less. 3 . The carbon nanotube dispersion according to claim 2 , having a first fiber diameter distribution in a range of 0.5 nm or more and less than 3 nm, and a second fiber diameter distribution in a range of 3 nm or more and 10 nm or less.

4. The carbon nanotube dispersion according to claim 1, wherein The dispersant includes a fluorine-based resin.

5. The carbon nanotube dispersion according to claim 4, wherein The mass ratio of the fluorine-based resin to the carbon nanotubes is 0.1 to 10.

6. The carbon nanotube dispersion according to claim 1, wherein The solvent does not substantially contain water, and has a pH of 8 to 12. 7 . A composite material slurry for an electrode, comprising the carbon nanotube dispersion according to claim 1 , and an electrode active material. 8 . An electrode film comprising a coating film of the carbon nanotube dispersion according to claim 1 or the composite material slurry for an electrode according to claim 7 . 9 . A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the electrode film according to claim 8 is used for at least one of the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Carbon nanotube film, its production method and capacitor using the same

    JP2008044820A

  • Electrode for lithium ion battery and its manufacturing method

    JP2010238575A

  • Electrode composition for battery

    JP2016025077A

  • Inspection device

    JP2022099875A

Cited By

  • Composite material, bolometer, and composite material forming method

    US12730009B2